PHENOMENOLOGY STUDY : ADOLESCENT WITH PREGNANCY EXPERIENCE IN PURWODADI COMMUNITY HEALTH CENTRE - Nanik Kurniawati; Retty Ratnawati; Fransiska Imavike Fevriasanty (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2019)
Adolescence pregnancy will have physical and psychological effects and include high-risk obstetric clients. Adoloscent with pregnancy has different adaptive abilities, but adolescents with pregnancy are expected to take care as early as possible so that maternal and fetal complications can be prevented, but the reality is that access to health services is often too late. The purpose of this study was to find out the experience of adolescents with pregnancy. The study design was qualitative interpretation phenomonology approach. Indepth interviews using semistructured questions involving six pregnant adolescents. Data were collected and analyzed using thematic analysis with Braun & Clarke approach. The research bring out six sub-themes were, the sense when the first time knowing pregnance, the variation of adaptation process, the sense of deal with childbirth, the support of problem solving, the obstacle of problem solving and the expectation for healthy life. The whole of six sub-theme became 1 theme was, the meaning of unpreparedness. Base on this research the most way that using by 6 participants for getting the meaning of unpreparedness in their pregnancy were hoping family support except become surrender. Kinds of support that expect were instrumental support, emotional and information support during pregnancy, preparation for childbirth, and preparation for become a parents. The result of the overall interview participants showed one of Â things that supporting achieve of unpreparedness meaning of adolescent with pregnancy was the absence psycical preparation, mentally, social, economy, and spritual. Commonly, base on this condition the adolescent hopefully great support expecially from their family, so they can deal with pregnancy condition, deal to childbirth up to become a parents after the baby come into the world.